Antipyretic And Antiinflammatory Activities Of Bopot Leaf Extract From Kutai Kartanegara District - Chaerul Fadly Mochtar; Novia Misnawati Aisyiyah; Qur’anni Akhwatun Husna; Hasyrul Hamzah; Muh Irham Bakhtiar; Reni Selviana Devi; Fathiah Putri Varizza; Ayu Faradillah; Elva Hafidzah; Suriati Suriati; Nur Lutfiah Damis (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Fever, a condition where the body temperature is above normal (> 37°C) can occur due to inflammation, an immune system response from harmful stimuli such as pathogens. Bopot leaves (Tabernaemontana divaricata) contain flavonoids, tannins, saponins and alkaloids which are thought to play a role in inhibiting prostaglandin synthesis (PGE2). This research was conducted to determine the antipyretic and anti-inflammatory activity of Bopot leaves. In vivo testing was used in mice (Mus musculus). The antipyretic test used peptone induction and rectal temperature was measured using a digital thermometer, while the anti-inflammatory test was carrageenin induced and the volume of edema was measured using a plethysmometer. Measurements were made before and after induction with an interval of 30 minutes for 2 hours. Results were analyzed by ANOVA using SPSS. The antipyretic test showed that the dose of 200 mg/Kg BW had the best antipyretic activity with an antipyretic power of 90.20% and the best anti-inflammatory activity at a dose of 250 mg/Kg BW. Bopot leaves contain flavanoid compounds which have antipyretic and anti-inflammatory effects by inhibiting cyclooxygenase (COX) which triggers prostaglandins that cause an increase in body temperature and inflammation. It was concluded that Bopot leaf extract has antipyretic and anti-inflammatory activity.